Slang Words Used in Lao Online Media - SEEPHARLAR, Chindar (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The study of slang words used in Lao online media aims to analyze the nature of slang words in Lao online media through a qualitative approach, utilizing descriptive and analytical methods. Data were collected from popular Facebook pages with over 100,000 followers that were active between January and October 2024. The findings revealed two main characteristics of slang words in Lao online media: structural slang and slang with special features. Structural characteristics were further divided into four subcategories: word combination, word repetition, word addition, and word truncation. Special characteristics were categorized into three subcategories: unconventional spelling, the use of quotations, and abbreviations.